IMPLEMENTASI LOGIKA FUZZY DALAM RECRUITMENT ASISTEN LABORATORIUM MENGGUNAKAN METODE C-MEANS (STUDI KASUS: TEKNIK INFORMATIKA UNIVERSITAS TANJUNGPURA) - Islamiati, Rizkya Bina (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
Clustering is the process of grouping the data into classes or clusters so that the data in a cluster has a high degree of similarity to one another but very different from the data in another cluster. There are some data that must be managed in a system that makes data service students, academic potential test data, calculation of fuzzy cmeans logic, and classification of student skills. This laboratory assistant recruitment system can assist in recruiting staff and faculty lab assistant. This system was developed using the programming language PHP with My SQL database. So that the system in the form of web site development. The purpose of this study is to produce a laboratory assistant recruitment application based website and using fuzzy logic with c-means method. The output of this application form of the cluster candidates laboratory assistants, and data used in this application is only of academic data and the data of the student's academic potential Prodi Information Engineering University Tanjungpura the register. Based on the results of user testing using Likert scale on the level of access of applicants obtained an average value of 20.36, at the Administrator level obtained value 53, and the level of the head of the laboratory obtained an average value 21. This value indicates that the lab assistant recruitment system using fuzzy c -means very good to be implemented.